(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
This paper aims to empirically demonstrate the J curve and determine the effect of the devaluation of the exchange rate on the balance of trade surplus in Nicaragua. For this purpose, we developed an econometric model, founded on distributed lag models "Almon" for time series. Correspondingly, this assay employs the structure calculation given by Shirley Almon (1965), and follows the proposed ordinary minimum square estimation restricted implemented by Schmidt and Waud (1973), and Giles (1975). The result can confirm the presence of the curve J for the Nicaraguan economy, whose effect lasts approximately two periods, the volume impact is presented in quarters one, two and three post generated devaluation in the exchange rate, ended quarters comprising the volume effect, negative effects arise very significant. Consequently, the proposed model is suitable for estimating the curve J in the Nicaraguan economy and the real exchange rate follows a fourth-degree polynomial distribution and the current political change slide 5 percent annually, has had a positive effect in the balance of trade balance in the long term.